2007
DOI: 10.1577/a05-098.1
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Scale System for the Mass Production of Rotifers Using Algal Paste

Abstract: Rotifers are a dominant zooplankton that are a preferred prey for some larval fish and are used by culturists during larval fish culture. The rotifer Brachionus plicatilis is a brackish‐water species suited for mass culture because it is prolific and can tolerate a wide variety of environmental conditions. Although the culture of this rotifer has been well documented, little information is available regarding the use of concentrated algal paste for the production of B. plicatilis. Thus, we investigated algal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The technology to raise hybrid striped bass from fry through the first 14-21 d posthatch (dph) in indoor tanks has been developed (Denson and Smith 1997;Ludwig 2006) as have tank systems for larval fish production of a wide variety of species, such as grouper (Serranidae) (Tucker 2005), snappers (Lutjanidae) (Watanabe et al 2005), lingcod Ophiodon elongates (Rust et al 2005), and hybrid striped bass (Ludwig 1994a(Ludwig , 2003(Ludwig , 2005(Ludwig , 2006. Indoor tank systems to culture rotifers as first-feed sources for tank production indoors have also been developed (Pfeiffer and Ludwig 2007).…”
mentioning
confidence: 99%
“…The technology to raise hybrid striped bass from fry through the first 14-21 d posthatch (dph) in indoor tanks has been developed (Denson and Smith 1997;Ludwig 2006) as have tank systems for larval fish production of a wide variety of species, such as grouper (Serranidae) (Tucker 2005), snappers (Lutjanidae) (Watanabe et al 2005), lingcod Ophiodon elongates (Rust et al 2005), and hybrid striped bass (Ludwig 1994a(Ludwig , 2003(Ludwig , 2005(Ludwig , 2006. Indoor tank systems to culture rotifers as first-feed sources for tank production indoors have also been developed (Pfeiffer and Ludwig 2007).…”
mentioning
confidence: 99%
“…Likewise, all other treatments with the exception of the preserved Nanno product were observed to support growth of the worms. The reasons for the poor performance resulting from the use of the preserved Nanno remains unclear as this product is successfully being used for the culture of rotifers and as a replacement for live algae used in greenwater larval culture systems and without any adverse affects (Sicuro et al 2006; Pfeiffer and Ludwig, 2007; Fairchild et al 2009). Fatty acid analysis revealed that preserved Nanno had a higher content of EPA but an overall similar spectrum of fatty acids as the live Nanno.…”
Section: Discussionmentioning
confidence: 99%
“…Nannochloropsis spp. may also be used as cell reactors for the production of heterologous proteins (Chen et al 2008) and have long been used as a food source in aquaculture (Duerr et al 1998;Pfeiffer and Ludwig 2007;Patil et al 2007;Ferreira et al 2009).…”
Section: Practical Importancementioning
confidence: 99%